Comment On S. Sarac And C. Sensogut?s Paper: A Statistical Determination Of Methane Emission From Coalbeds - Case Study - SAIMM Journal, 103, No. 3. 2003. Pp. 209?211 - P. J. D. Lloyd (The Southern African Institute of Mining and Metallurgy, 2004)
At first I read this paper with interest, which grew to fascination, and ended up with horror. Such reactions to a supposedly scientific contribution are rare, and I believe the coal mining community must be warned in the strongest possible terms against the recommendations that this paper makes. The paper purports to have assessed statistically two sets of data on methane concentrations recorded in the return air from Turkish longwalls. The first set of data, from their Table I, is reproduced in Table I below. The data have been rearranged in classes to indicate the underlying distribution. While there is only limited data (N=33), the distribution looks as if it could be the sum of two normal distributions with means around 0.5 and 0.8, or possibly a log-normal distribution. What is quite clear is that it is nota single normal distribution.